Get Programming video edition - Bell, Ana (Manning Publications, 2018)
Accessible and intuitive. After going through the many examples in the book, I felt much more confident in my Python programming skills. Nicole Kogan, MIT Get Programming: Learn to code with Python introduces you to the world of writing computer programs without drowning you in confusing jargon or theory that make getting started harder than it should be. Filled with practical examples and step-by-step lessons using the easy-on-the-brain Python language, this video book will get you programming in no time! This book works perfectly alongside Ana Bell's liveVideo course Get Programming with Python in Motion, featuring more projects and skills for you to pick up with this great language! about the technology Let's face it. The only way to learn computer programming is to do it. Whether you want to skill up for your next job interview or just get a few pet projects done, programming can be an amazing tool. This book is designed especially for beginners, helping them learn to program hands on, step by step, project by project. It's time to get programming! about the book Get Programming: Learn to code with Python teaches you the basics of computer programming using the Python language. In this exercise-driven video book, you'll be doing something on nearly every page as you work through 38 compact lessons and 7 engaging capstone projects. By exploring the crystal-clear illustrations, exercises that check your understanding as you go, and tips for what to try next, you'll start thinking like a programmer in no time. what's inside Programming skills you can use in any language Learn to code - no experience required Learn Python, the language for beginners Dozens of exercises and examples help you learn by doing about the audience No prior programming experience needed. about the author Ana Bell is an MIT lecturer and scientist who teaches the popular course, Introduction to Computer Science and Programming Using Python. A definitive resource for anyone wanting to grasp how to solve problems using Python. Vester Thacker, AIG Technologies Very helpful in creating a solid foundation of generic programming principles. Prabhuti Prakash, Atos Kick-starts programming concepts with Python-but useful to anyone getting started with programming. Sam Johnson, Intouch Solutions NARRATED BY MARK THOMAS.
Online resource; Title from title screen (viewed March 27, 2018)
Keywords: Electronic videos; local